Polarization independent 2×2 multimode interference coupler with bricked subwavelength metamaterial - Pérez-Armenta, Carlos; Ortega-Moñux, Alejandro; Luque-González, José Manuel; Halir, Robert; Reyes Iglesias, Pedro José; Schmid, Jens H.; Cheben, Pavel; Molina-Fernández, Íñigo; Wanguemert-Pérez, Juan Gonzalo (My University, 2022)
The silicon-on-insulator (SOI) platform enables high integration density in photonic integrated circuits while maintaining compatibility with CMOS fabrication processes. Nevertheless, its inherently high modal birefringence hinders the development of polarization-insensitive devices. The dispersion and anisotropy engineering leveraging subwavelength grating (SWG) metamaterials makes possible the development of polarization agnostic waveguide components. In this work we build upon the bricked SWG metamaterial nanostructures to design a polarization independent 2×2 multimode interference (MMI) coupler for the 220 nm SOI platform, operating in the telecom O-band. The designed device exhibits a 160 nm bandwidth with excess loss, polarization dependent loss and imbalance below 1 dB and phase error lower than 5°.
Keywords: Telecomunicaciones - Equipos y material; Circuitos integrados; Subwavelength grating metamaterial waveguide; Multimode interference coupler; Polarization independent; Photonic integrated circuit